Letter from the U.S. Department of Justice Immigration and Naturalization Service to Max Bredig, March 13, 1943 - United States. Immigration and Naturalization Service (1943)
The U.S. Department of Justice Immigration and Naturalization Service informs Max Bredig (1902-1977) that he needs to provide where he has lived and worked in the last seven years.
Keywords: United States. Immigration and Naturalization Service; Bredig, Max Albert, 1902-1977